1999
DOI: 10.1002/(sici)1097-0215(19990129)80:3<380::aid-ijc8>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of tumor killing using a combination of tumor immunization andHSV-tk suicide gene therapy

Abstract: Tumor cells genetically modified with the herpes simplex virus thymidine kinase (HSV‐tk) gene in combination with ganciclovir (GCV) demonstrate a “bystander effect”. Previous attempts to enhance the bystander tumor killing by combining cytokine genes with HSV‐tk/GCV have met with varying results. The present study was designed to determine the effects of tumor immunization in combination with HSV‐tk gene‐modified tumor cells and GCV on tumor killing and to determine if the bystander tumor killing could be enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In one example, immunization to tumor cells before treatment with the HSV-TK gene-modified cells and GCV resulted in prolonged animal survival. 14 Our results confirm and extend previous findings using IFN 15,16 by demonstrating the importance of this combination in a therapeutic tumor model and analyzing the underlying mechanism that leads to a synergistic antitumor effect. We have demonstrated that a low dose of IFN␣2a decreased the IC 50 of GCV from 0.03 M to 0.005 M in PA1STK cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In one example, immunization to tumor cells before treatment with the HSV-TK gene-modified cells and GCV resulted in prolonged animal survival. 14 Our results confirm and extend previous findings using IFN 15,16 by demonstrating the importance of this combination in a therapeutic tumor model and analyzing the underlying mechanism that leads to a synergistic antitumor effect. We have demonstrated that a low dose of IFN␣2a decreased the IC 50 of GCV from 0.03 M to 0.005 M in PA1STK cells.…”
Section: Discussionsupporting
confidence: 88%
“…Weeks after therapy, the dying GCV-exposed HSV-TK tumor cells lead to a delayed hypersensitivity immune response, because GCV is not immunosuppressive. 9,14 Thus, studies with IL-2 in combination with GCV therapy did not enhance the early phase bystander killing but did enhance the later long-term tumor immunity. Therefore, it would be expected that cytokines that enhance the early phase of the bystander effect (proinflammatory) would enhance the antitumor response.…”
Section: Discussionmentioning
confidence: 98%
“…Expressed TNF-α activated and enhanced the proliferation of T lymphocytes, and combination of TNF-α can synergistically stimulate the anti-tumor immune response in vivo. [28][29][30][31] The experimental results confirmed that tk-TNF-α /GCV gene therapy could kill tumor cells markedly. If combined with TNF-α gene, they could boost the antitumor reaction, and produce powerful anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies demonstrated this effect to be only present in vivo in immunocompetent animals, but not in immunodeficient mice. [7][8][9][10][11][12] It is believed that HSVtk suicide gene therapy converts an immunoinhibitory environment into an immunostimulatory microenvironment. 13 The use of viral vectors is complex and costly.…”
Section: Introductionmentioning
confidence: 99%